'Bacteroides ihuae' sp. nov., a new bacterial species isolated from the human respiratory microbiome. (May 2017) - Fonkou, M.D.M.; Morand, A.; Fournier, P.-E.; Raoult, D.; Dubourg, G.
Abstract: We present the main features of 'Bacteroides ihuae' sp. nov., strain Marseille-P2824 T (CSUR P2824), isolated from the sputum of healthy Frenchwoman living in Marseille.